Orquinha dos Juncais (vila Nova de Paiva, Viseu) : análises polínicas - López Sáez, J. A.; Cruz, D. J. da (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In this paper we are publishing the results of the pollen analyses of Orquinha dos Juncais. It is a monument with a tumulus built on the limits of a depressed ground; it has a small chamber in the centre, probably rectangular in shape; judging by its dimensions, it concerns an individual burial or, at least, a burial of restricted utilization. The burial, located near Orca dos Juncais (a large passage grave monument), was built most likely during the second half of the IV millennium BC.